Anomaloterga mantiqueirae: a new genus and species of Strogulomorphini from the Mantiqueira fault escarpment, Brazil (Orthoptera, Phalangopsidae, Strogulomorphini). - Bolfarini, Marcio Perez; Mello, Francisco de Assis Ganeo de [UNESP] (Pensoft Publishers, 2010)
A new genus and species of cricket, Anomaloterga mantiqueirae, here described, is the first representative of Strogulomorphini to be reported from Brazil. The specimens were collected at night from the lower portions of live tree trunks in a summit forest located on the Mantiqueira Fault Escarpment, State of São Paulo.